Testicular immunosenescence: a key player in age-related spermatogenic decline - Zhan, Ming-Wei; Zhou, Mu-Hua; Zhao, Bin-Bin; Bao, Xiao-Jie; Chen, Yibo; Zhu, Jingyu (Frontiers in Cell and Developmental Biology, 2025)
As global populations age, testicular aging has become a key contributor to the gradual decline in male fertility, characterized by lower sperm count, poorer sperm quality, and reduced reproductive potential. While the testis is traditionally viewed as an immune-privileged site, growing evidence shows that this immune protection weakens over time—a process now known as testicular immunosenescence. This review provides a comprehensive overview of age-related changes in the testicular immune landscape. These include the depletion of CD4+ and CD8+ T cells, dysfunction of regulatory T cells (Tregs), abnormal polarization of macrophages, and the breakdown of the blood–testis barrier (BTB). Together, these changes lead to chronic low-grade inflammation and disrupt the delicate environment required for healthy sperm production. In addition, we explore how immune aging is closely linked to metabolic changes, especially within Sertoli and Leydig cells. These intertwined processes form a feedback loop—an “immune–metabolic axis”—that accelerates germ cell death and impairs spermatogenesis. We also discuss emerging treatment strategies, such as anti-inflammatory therapies, mitochondrial support, and NAD+ precursor supplementation, which may help preserve testicular function and male fertility with age. By framing testicular immunosenescence as both a driving mechanism and a potential therapeutic target, this review opens up new directions for tackling age-related male reproductive decline.